Faktor- Faktor Yang Mempengaruhi Kejadian Stunting Pada Balita Di Indonesia Tahun 2024 - Eka Oktavia; Yulia Vanda Editia; Mahardika Primadani (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Stunting caused by malnutrition during the growth and development process has a higher risk of illness and death in adulthood, so it can hamper motor skills and reduce the level of productivity and competitiveness of a nation (Rahmadhita, 2020). National nutritional status survey data (SSGI) in 2022, the prevalence of stunting was 21.6%. The target stunting rate in Indonesia is 14% in 2024 and the WHO standard target is below 20%, therefore how important it is to handle stunting in Indonesia. The aim of this research is to determine the factors that influence the incidence of stunting in toddlers. The method in this research is a full text critical review in Indonesian. Articles were selected in stages using the appraisal tool preferred reporting items for systematic reviews and meta analyzes (PRISMA), then duplicate filtering was carried out, screening was carried out based on title and abstract, full text, feasibility studies and until the final stage 11 articles were found that met the inclusion and study criteria. appropriateness. The results of this research show that the factors that influence the incidence of stunting in toddlers are exclusive breastfeeding, low birth weight, infectious diseases, mother's height, mother's education, family income, and nutritional status of pregnant women.